2021
DOI: 10.5603/cj.a2019.0052
|View full text |Cite
|
Sign up to set email alerts
|

ST2 in patients with severe aortic stenosis and heart failure

Abstract: Background: ST2 is a circulating biomarker that is well established for predicting outcome in heart failure (HF). This is the first study to look at ST2 concentrations in optimally treated patients with stable but significant left ventricular systolic dysfunction (LVSD) compared to patients with severe aortic stenosis (AS). Methods: Two cohorts were retrospectively studied: 94 patients undergoing transcatheter aortic valve implantation for severe AS (63 with normal ejection fraction [EF] and 31 with reduced E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Fabiani et al [126] found that sST2 ≥ 284 ng/mL had the best accuracy for predicting altered global longitudinal strain in patients with severe AS. However, sST2 levels before TAVR were not significantly different between HF patients and AS patients with normal EF (EF ≥ 50%) [127]. Therefore, there were no correlations between sST2 levels and NT-proBNP concentration and parameters of AS severity [128].…”
Section: Biomarkersmentioning
confidence: 85%
“…Fabiani et al [126] found that sST2 ≥ 284 ng/mL had the best accuracy for predicting altered global longitudinal strain in patients with severe AS. However, sST2 levels before TAVR were not significantly different between HF patients and AS patients with normal EF (EF ≥ 50%) [127]. Therefore, there were no correlations between sST2 levels and NT-proBNP concentration and parameters of AS severity [128].…”
Section: Biomarkersmentioning
confidence: 85%
“…Based on these limitations, more novel biomarkers are being studied to assess HF conditions, including sST2, GDF15, and IL-6. In the present study, we chose sST2 as a novel biomarker that contributes to the formation of myocardial fibrosis and ventricular remodeling [14,[21][22][23][30][31][32][33]. Since its discovery in 1989, increasing studies have confirmed that cardiomyocytes and cardiac fibroblasts induce release of both lST2 and sST2 when subjected to mechanical stretching in HF patients and in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery in 1989, increasing studies have confirmed that cardiomyocytes and cardiac fibroblasts induce release of both lST2 and sST2 when subjected to mechanical stretching in HF patients and in animal models. e predictive value of sST2 among HF patients has been revealed in several studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Interestingly, our best cutoff point of sST2 as a long-term mortality predictor in this study was 43.42671 ng/ml, which is greater than the traditional cutoff level of 35 ng/ml, possibly due to the additional protection of ICD therapy along with optimal medication, in these high-risk heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ST2 is a receptor of the IL‐33 and consists of two common subtypes: sST2 and ST2L. ST2L is the specific IL‐33 receptor and is mainly expressed on the Th2 and mast cells, whereas the sST2 is the decoy receptor that negatively regulates the IL‐33/ST2 pathway 10–13 …”
Section: Introductionmentioning
confidence: 99%